Planning and Implementation of Innovative Da'wah by BKPRMI: Strengthening Religious Development of Youth in Tanjung Tiram - Sopy, Akbar Tarmizy; Haikal, Muhammad Fachran (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research discusses the planning and implementation of innovative da'wah carried out by the Indonesian Mosque Youth Communication Agency (BKPRMI) in an effort to strengthen youth religious development in Tanjung Tiram District. Adolescents are one group that requires special attention in religious formation. However, the challenges faced in presenting da'wah that is relevant to current developments are something that cannot be ignored. The method in this research uses a descriptive qualitative approach. This research reveals effective strategies implemented by BKPRMI in carrying out da'wah that is relevant to current developments. The research results show that BKPRMI has carried out careful planning in facing challenges and BKPRMI has implemented various innovations in da'wah, such as the use of digital media, mentoring programs and social religious activities specifically designed to attract the interest of teenagers. Apart from that, collaboration with schools, local communities and parents is also the key to success in this coaching program. The challenges faced include limited resources, resistance from some teenagers, and lack of support from several related parties.